Electrospun Silk Nanofibre Mats and Their Potential as Tissue Scaffolds - Mohammadzadehmoghadam, Soheila (Curtin University, 2018)
In this study new electrospun silk fibroin (SF) based scaffolds were developed and their material and biocompatibility characteristics evaluated. Three types of SF based scaffolds were generated: SF/halloysite (HNT), SF/gelatin and SF/collagen. Scaffolds chosen for their material and biocompatibility characteristics were coated with fibroblast extracellular matrix and their efficacy for supporting primary human keratinocyte expansion were investigated. Collectively these data indicated SF/HNT scaffolds have merit for wound healing and tissue engineering applications.